202k views
2 votes


2x+3y=6
−4x+3y=12


1 Answer

3 votes

The best way to start off this question is to get rid of the y value as the y value is already equal in both equations. T
-1o get rid of the y value, subtract the 2 equations together.


6x=-6


x=-1

Now that you have solved x, you can replace any x value (from either equation). In this scenario, the first equation is easier to solve for the y value.


2(-1)+3y=6\\-2+3y=6\\3y=8\\y=(8)/(3)

Thus,

x =
-1 and y =
(8)/(3);
(-1,(8)/(3) )

Hope this helped :)

User Joe Mastey
by
5.5k points